The Empowerment of Red Onion Farmers in Increasing Multiplier Effect of Income - Catur Prabowo; Sucihatiningsih Dian Wisika Prajanti; Dwi Cahyaningdyah (Economics Development Analysis Journal, 2022)
The problem in this study is that many red onion farmers in Brebes Regency are still not prosperous because the red onion farming that is being carried out is still inefficient, so they cannot provide optimal results. This study aims to analyze the efficiency level of red onion farming in the Brebes Regency and formulate strategic priorities for improving the welfare of red onion farmers in the Brebes Regency. The analytical method in this study is a mixed method between quantitative descriptive, namely the Cobb - Douglas production function with a stochastic frontier approach. The second analysis technique used is Analytical Hierarchy Process (AHP). The result shows that the average value of the technical efficiency of red onion farming is 0.718. Reducing the use of production factors in red onion farming can be done by reducing the use of production factors of NPK fertilizers and pesticides. The calculation result of the price efficiency of the production factor used is still more than 1, which is 46.60. The result obtained from the calculation of economic efficiency for red onion farming in the Brebes Subdistrict is 33.45. The calculation result of the economic efficiency is more than 1, meaning that red onion farming in Brebes Subdistrict is not yet economically efficient. The most prioritized criterion in empowering red onion farmers in Brebes Regency is government policy, with a weight value of 33.3%. The most prioritized alternative in the Shallot Farmer Empowerment Strategy in Brebes Regency is the policy support for determining the cost of goods sold with a weight value of 17.4%.